ANALISIS BIBLIOMETRIK SUSTAINABLE HALAL SUPPLY CHAIN PADA INDUSTRI KECIL MENENGAH - Fajrah, Nofriani; Putri, Nilda Tri; Fatrias, Dicky (Universitas Putera Batam, 2025)
The manufacturing industry sector, especially Small and Medium Industries (SMEs), faces major challenges in increasing competitiveness, especially related to the dynamic changes in the global supply chain and the need for halal food products. This study aims to analyze research trends related to Sustainable Halal Supply Chain (SHSC) using a bibliometric analysis approach. Using data from the Scopus database, this study identifies relevant scientific publications and examines the contributions of various countries, authors, and journal sources on this topic. The results of the analysis show that research related to SHSC has grown rapidly after 2018, driven by increasing attention to sustainability and global market demand for environmentally friendly halal products. Countries such as Malaysia and Indonesia lead publications on this topic, focusing on the integration of halal principles and sustainability in the supply chain. Despite a significant increase in publications, most of the research is still conceptual, with a lack of empirical data, especially outside Southeast Asia and the Middle East. This study proposes to increase empirical-based studies, especially in Indonesia, to understand the challenges and opportunities in implementing SHSC. This study provides insight into the development and direction of SHSC research, as well as its contribution to economic, social, and environmental sustainability in the halal food industry.